The Effect Of Target Muscle Weight Training On The Increase Of Tesoserone and Growth Hermones In Advance Bodybuilders - Abedulsattar, Muhanned; Hanoon, Wasan; Taha, Ahmed (Journal of Physical Education, 2017)
The problem of the research lies in identifying the relationship between weight exercise and testosterone and growth hormones concentration levels in weightlifters as well as bones longitudinal ability and muscle strength. The aim of the research is designing target muscle weight exercises for advance weightlifters as well as identifying the effect of these exercises on testosterone concentration level in advance weightlifter without using steroids. In addition to that the researchers aimed at identifying the effect of these exercises on growth hormone concentration in advance weightlifters. The researcher used the experimental method. The subjects were (5) weightlifters from Al Shorta club season 2015 – 2016. The data was collected and treated using proper statistical operations. The researchers concluded that testosterone and growth hormones increase after physical effort using weights in chest, abdominal and shoulders. These hormones are necessary for muscle building during training sessions that do not exceed 45 – 60 strength training with high intensity 85 – 95% during long rests more than 120 sec.